Distribution of Megabenthic Communities Under Contrasting Settings in Deep-Sea Cold Seeps Near Northwest Atlantic Canyons - Cleland, Jason; Kazanidis, Georgios; Roberts, J. Murray; Ross, Steve W. (Frontiers in Marine Science, 2021)
Cold seeps support fragile deep-sea communities of high biodiversity and are often found in areas with high commercial interest. Protecting them from encroaching human impacts (bottom trawling, oil and gas exploitation, climate change) requires an advanced understanding of the drivers shaping their spatial distribution and biodiversity. Based on the analysis of 2,075 high-quality images from six remotely operated vehicle dives, we examined cold seep megabenthic community composition, richness, density, and biodiversity at a relatively shallow (∼400 m water depth) site near Baltimore Canyon (BC) and a much deeper site (∼1,500 m) near Norfolk Canyon (NC), in the northwest Atlantic. We found sharp differences in the megabenthic composition between the sites, which were driven mostly by bathymetric gradients. At both BC and NC there were significant differences in megabenthic composition across habitats. Hard habitats in and around cold seeps had significantly higher values of species richness, density, and biodiversity than soft habitats. Depth and habitat complexity were the leading environmental variables driving megabenthic variability. The presence of microbial mats and gas bubbling sites had a statistically significant contribution to explaining megabenthic variability mainly in the shallower BC and less in the deeper NC areas examined; drivers behind this discrepancy could be related to differences between BC and NC in terms of chemical compound fluxes and megafaunal life history characteristics. Our surveys revealed marine litter, primarily from commercial fisheries. This study highlights the importance of habitat complexity for the proliferation of highly diverse cold-seep ecosystems and underscores the importance of discovery science to inform spatial management of human activities in the deep and open ocean.